Porphyromonas bennonis sp. nov., isolated from human clinical specimens - Summanen, Paula H.; Lawson, Paul A.; Finegold, Sydney M. (International Journal of Systematic and Evolutionary Microbiology, 2009)
During our investigation of the bacteriology of human wound infections and abscesses, a novel anaerobic, non-spore-forming, Gram-negative bacillus was frequently isolated. On the basis of morphological and biochemical criteria, the strains were tentatively identified as belonging to the family Bacteroidaceae, but they did not appear to correspond to any recognized species of this family. Comparative 16S rRNA gene sequencing showed that the 14 novel strains were genotypically homogeneous and confirmed their placement in the genus Porphyromonas. Sequence divergence values >10 % with respect to reference Porphyromonas species demonstrated that the strains isolated represent a novel species. On the basis of biochemical criteria and phylogenetic considerations, it is proposed that these strains isolated from human sources should be assigned to a novel species of the genus Porphyromonas, named Porphyromonas bennonis sp. nov., with WAL 1926CT (=ATCC BAA-1629T =CCUG 55979T) as the type strain.